The Effect of Macrozoobenthos Diversity Module based on Problem-based Learning on Junior High School Students’ Environmental Attitudes - Sueb, S.; Damayanti, J. (Jurnal Pendidikan IPA Indonesia, 2021)
It is necessary to build students’ responsibility character when dealing with life problems such as environmental pollution. Because there is much pollution, it is important for students to analyze the condition of the polluted environment because they are expected to overcome the problems. The effort made is to teach students using problem-based learning modules. This module contains material of macrozoobenthos diversity as bioindicators of river water quality. This study aims to determine the effect of macrozoobenthos diversity as a bioindicator module based on problem-based learning on students’ environmental attitudes. The research design is quasi-experimental using a nonrandomized control group pretest-posttest design. The sample in this study was 60 students divided into experimental class and control class. The test results showed that the significance value for PBL modules is 0,016 ≤ 0.005, so the hypothesis is accepted. There is a difference between students who use the PBL module, which improves students’ environmental attitudes than science textbooks. Students’ initial environmental attitudes also influence it.